MOSCOW-ANKARA-TEHRAN: A TRIPARTITE TACTICAL ALLIANCE IN THE SYRIAN CRISIS - VAKHSHITEH, Ahmad Naser; LAPENKO, Marina; OSPANOVA, Aigerim (CENTRAL ASIA AND THE CAUCASUS, 2024)
In the last decade, the Syrian civil war, which began as an internal political crisis, developed into an international crisis with all influential world actors involved to different degrees, or even a war of a new type, endowed with the elements of a proxy war, a hybrid war, an irregular war, and an asymmetric war.The Syrian crisis changed the balance of power in the Middle East; it strongly affected foreign policy strategies of regional and extra-regional players and created new coalitions and alliances that light terrorism and transnational security threats.Russia could not stay away from the Syrian settlement: its involvement suited its national interests and the resolution to play a much greater role on the international arena; it was implied by potential threats, the spread of terrorism and extremism, and the changed balance of power in the MiddleEast. Having discovered that efficient cooperation with the United States was impossible, Russia set up an operational task group that comprised Russia, Turkey, and Iran, a tripartite alliance of sorts.The paper examines how the mechanism of interaction between Russia, Turkey, and Iran took shape in the context of crisis resolution in Syria; the authors conclude that this is a tactical union rather than a strategic military alliance. These countries combined forces to prevent Syrian disintegration and its geopolitical weakening, as well as to consolidate their positions in the region. Despite serious disagreements, the allies have achieved compromises on many issues. Russia, Turkey, and Iran have already resolved many ad hoc problems and have positively affected the course of Syrian settlement, bringing peace closer at the negotiation table.